The morphological types and arrangement of cone cells, and the visual acuity of sutchi catfish pangasianodon hypophthalmus - Nai, Han Tan; Mukai, Yukinori (2015)
In this study, the morphological types and arrangement of cone cells, and the visual acuity of sutchi catfish Pangasianodon hypophthalmus were determined to obtain fundamental understanding of its vision. The left eyes of the adult sutchi catfish were fixed in Bouin’s solution and were cut into 17 regions. The 17 regions were then immersed in a series of ethanol, cleared with histolene, embedded in paraffin, cut into 6 μm thick tangential sections, and stained with haematoxylin-eosin. Only single cone cell was identified and the area around the bottom region showed tendency of higher density of single cone cells.